Form of Verifying Affidavit in a Matrimonial Cause: Substantial or Strict Compliance? : Kano Bar Journal - Tijani, Nasiru (Afrischolar Discovery Repository (Annex), 2016)
Visit www.afrischolarrepository.net.ng for more publications.